2021
DOI: 10.1037/pne0000274
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of visual processing speed to visual and auditory working memory in early school years.

Abstract: Objective: The primary aim of the present study was to examine the predictive contribution of age and speed of visual processing measures to the determination of visual working memory (VWM) and auditory working memory (AWM) in children aged 5–7 years. Method: The present study has used structural equation models (SEM) for determination of speed of visual processing measures (visual inspection time, visual–verbal rapid automatic naming of objects, and a visuo-motor game-like iPad application) to working memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
1
4
1
Order By: Relevance
“…There are presently no models of WM that argue for discrete types of processing (i.e., verbal, visual, spatial). However, findings from a recent study by Alghamdi et al (2021) suggest that visual processing ability relates only to the development of visual WM and not verbal WM in 5- to 7-year-olds, supporting the suggestion here that types of processing within WM might be discrete. As the Alghamdi et al study only examined visual processing ability, there is value in further investigating visual, spatial and verbal processing to understand links with the development of the respective storage abilities in WM.…”
Section: Discussionsupporting
confidence: 79%
“…There are presently no models of WM that argue for discrete types of processing (i.e., verbal, visual, spatial). However, findings from a recent study by Alghamdi et al (2021) suggest that visual processing ability relates only to the development of visual WM and not verbal WM in 5- to 7-year-olds, supporting the suggestion here that types of processing within WM might be discrete. As the Alghamdi et al study only examined visual processing ability, there is value in further investigating visual, spatial and verbal processing to understand links with the development of the respective storage abilities in WM.…”
Section: Discussionsupporting
confidence: 79%
“…However, in our younger children (i.e. 7-years and under) who are still learning to read, verbal encoding and rehearsal strategies are reported to be unlikely (Hitch et al, 1988;Pickering, 2001;Alghamdi et al, 2021). It is therefore possible that some of the association between visually presented Digit Span and anxiety may be mediated by verbal encoding and rehearsal factors, although other aspects of our results suggest that the impact of such verbal encoding is small: for instance, the correlations between auditoryverbal and visual forward digit span (short-term memory) and backward digit span (working memory) are only moderate (0.49 for forwards and 0.59 for backwards), indicating that the two task modalities are at least partially differentiated.…”
Section: Limitations and Future Directionsmentioning
confidence: 63%
“…The custom visual digit span task has previously been used with a range of typical and atypical children (e.g. Mungkhetklang et al, 2016 ; Alghamdi et al, 2021 ) and may be considered a more reliable estimate of working memory (than auditory-verbal digit span) in populations with language difficulties ( Olsthoorn et al, 2014 ). Reliability in our sample was moderate to good in both the NT (Forward = 0.70; Backward = 0.82) and AHDN groups (Forward = 0.71; Backward = 0.84).…”
Section: Methodsmentioning
confidence: 99%
“…It was hypothesized, in line with past research [35,36], that older children would demonstrate both longer forward and backward digit spans, and faster MRTs on multisensory tasks [10,17]. It was also hypothesized that combined cognitive development as a measure of WM and IQ tasks would contribute further to MRTs of multisensory processing.…”
Section: Introductionmentioning
confidence: 70%
“…To assess fine visually driven motor (visuomotor) processing, the Lee-Ryan Eye-Hand Coordination Test battery (SLURP) was used [41]. It has been demonstrated that this task is reliable and valid for assessing visuomotor integration in both children and adults [18,35]. In this task, children were instructed to trace five shapes in order (circle, triangle, square, rabbit, and snail); the total time taken to accomplish the task was extracted and analysed for each child.…”
Section: Visuomotor Processing Using the Slurp Eye-hand Coordination Appmentioning
confidence: 99%